Contested Space: A Place on the Way to Collaborative Government? - Latta, Peter (Ethnologies, 2005)
The announcement in 1999 by the government of Newfoundland and Labrador of a new $40 million cultural heritage complex, known as The Rooms, to replace the crumbling buildings of the provincial art gallery, museum, and archives should have been greeted by celebration. Instead, a rancourous public debate ensued that threatened to cancel the project. That debate centred on government’s choice of an eighteenth century fort site for the new building. This article reviews the genesis of the project which caused the public dispute and traces the discussion as the contest for the building site unfolded. The Rooms controversy, and the events which eventually brought it to a close, powerfully illustrate the importance of public consultation to government decision-making in heritage matters. The debate vividly demonstrates how different interest groups claim authoritative voice around issues of heritage preservation and interpretation.